The impacts of diagnosis-intervention packet payment on inpatient medical costs for hematologic malignancies and solid tumors: evidence from a retrospective study in China - Xu, Huiping; She, Qunqing; Zhang, Beibei; Zhang, Shaogui; Xie, Linjun (Frontiers in Public Health, 2025)
BackgroundThis study aims to analyze and compare the impact of the diagnosis-intervention packet (DIP) payment on inpatient medical costs for hematologic malignancies (HM) and solid tumors (ST) patients, and to explore its implications for hospital financial sustainability and payment reform.MethodsUsing a retrospective research design, this study focused on HM and ST patients treated before and after the implementation of the DIP payment at a large tertiary general hospital in A city, located in the eastern coastal area of China. Data were collected, organized, and analyzed to compare differences in inpatient medical costs between HM and ST patients and to examine their impact on the income of the department of hematology.ResultsThe study included 5,115 cases from both before and after the DIP payment implementation. Post-implementation, the median inpatient medical costs per case decreased from 5,544.45 CNY to 5,169.66 CNY, with costs for both HM and ST hospitalizations showing a decline. Specifically, the inpatient medical costs per case for HM were 5,722.46 (4,471.08, 11,508.78) CNY, higher than those for ST at 4,779.28 (3,056.70, 7,152.64) CNY, and exceeding the DIP payment standard. Wilcoxon signed-rank test and regression analysis indicated that HM inpatient medical costs surpass the standard payments, resulting in financial losses. All findings were statistically significant (p < 0.05). These results suggest a structural mismatch between DIP reimbursement rates and the resource intensity of hematologic malignancy treatment, which may jeopardize the financial viability of hematology departments.ConclusionDespite a reduction in median inpatient medical costs following the implementation of the DIP payment, departments treating HM patients continue to experience financial losses due to costs exceeding the payment standard. These findings highlight the need to refine DIP payment standards to better account for clinical complexity and technological advancements. Future reforms should aim to improve alignment between payments and actual care needs to ensure financial sustainability and equity. However, this study is limited by its single-center design and lack of control for potential confounders. Broader multi-center studies with more detailed clinical data are needed to validate and extend these findings.